EMPOWERING LITERACY IN MARITIME EDUCATION: STRATEGIES AND PROFESSIONALISM ALIGNMENT - Sijabat, Panderaja Soritua; Simanjuntak, Marudut Bernadtua; Mudakir; Putrawan, Bobby Kurnia; Lumingkewas, Marthin Steven (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
This research investigates language instruction strategies and professionalism alignment within maritime education, focusing on 45 junior cadets. Through qualitative analysis, findings reveal varying language proficiency levels among cadets, with a predominant need for technical terminology mastery and communicative competence. Additionally, cadets emphasize the importance of practical learning experiences, such as shipboard training, and the integration of cross-cultural competence training. The research highlights the alignment between language instruction practices and international standards, notably the International Maritime Organization's (IMO) Standards of Training, Certification, and Watchkeeping (STCW) convention. Moreover, professionalism attributes, including safety awareness, ethical conduct, and leadership skills, are identified as integral components of maritime education. Recommendations include the integration of specialized language resources, continuous evaluation of instructional practices, and the promotion of ethical leadership. By addressing language instruction needs and professionalism requirements, maritime education institutions can enhance cadets' readiness for successful careers in the maritime industry.